Sperm whale mass stranding in Italy: gas and fat emboli analyses - Bernaldo De Quirós Miranda, Yara; Sacchini, Simona; González Díaz, Oscar Manuel; Muñoz Abellán,Barbara; Saavedra, Pedro; Mazzariol, Sandro; Fernández Rodríguez, Antonio Jesús (2011)
On the 10th of December of 2009, seven sperm whales were found beached in Gargano coast, Italy. There was a fast and coordinated stranding response that enabled a multidisciplinary study with the collaboration of several scientific institutions. Many hypotheses were considered and analyzed including the “gas and fat embolic syndrome”. For the first time, a standardized methodology for the study of gas embolism was applied to a mass stranding of sperm whales. Because of field work-conditions, complete necropsies, were only performed in the three sperm whales that stranded alive and survived beached for several hours. Gas bubbles were only found in the coronary veins. Bubbles were sampled with an insulin syringe and stored in a 5 ml vacutainer without additives. Analyses were done by gas chromatography. Results showed a composition of 70% of N2, 15% of CO2 and 15% of O2 in the freshest animal, in contrast with 30% of N2, 30% of CO2, 6% of O2 and 33% of H2 in the most decomposed animal. These results excluded putrefaction as the sole source of gas formation and dissection as artifact, since composition was not the same as the atmospheric air and bubbles were not found in other veins. Bubbles were not widely distributed, nor either massively, through out the rest of the body as described in the “gas and fat embolic syndrome”. Fat embolism was excluded because lung samples from all three sperm whales showed very few or none fat emboli (grade 0 or 1). These results on fat emboli confirmed that this evidence is not commonly found in stranded cetaceans, even if they spent hours stranded alive on the shores, differentiating this event with atypical mass stranding related to sonar exposure. Thus the “gas and fat embolic syndrome” was ruled out as the cause of the stranding.